IMPROVING ORGANIZATIONAL PERFORMANCE WITH ORGANIZATIONAL CULTURE AND TRANSFORMATIONAL LEADERSHIP THROUGH INTERVENING ORGANIZATIONAL COMMITMENT VARIABLES - Rahmatullah, Asep; David Ramdansyah, Agus; Kambara, Roni; Haryadi, Didit (Dinasti Publisher, 2022)
This study aims to examine and analyze the influence of organizational culture and transformational leadership on organizational performance through organizational commitment. This study uses a descriptive quantitative method with a causal approach. The object of this research is the regeneration of the Indonesian Democratic Party of Banten Province using a sample of 158 respondents. Questionnaire answers were measured using an interval scale of 1 – 10. Data were analyzed using the SmartPLS version 3.29 software. The results of this study stated that: 1). Organizational culture has a positive and significant effect on organizational performance. 2). Transformational leadership has a positive and significant effect on organizational performance. 3). Organizational culture has a positive and significant effect on organizational commitment. 4). Transformational leadership has a positive and significant effect on organizational commitment. 5). Organizational commitment has a positive and significant effect on organizational performance. Organizational commitment can mediate between organizational culture and transformational leadership in partial mediation.